An IT solutions company's shift for SAP ECC systems to SAP cloud-based solutions to build demands for resource and capability management; a technology foresight based on environmental scanning, cross-impact analysis, and trend extrapolation - Pagtalunan, Arvilind C.
The project uses technology foresight techniques, specifically environmental scanning, trend extrapolations and cross-impact analysis, to assess growth and decline in the core SAP ECC non-cloud systems, and its technology shift to SAP cloud-based systems. For a qualitative assessment, a cross-impact matrix was used to assess the impact and probability of the key variables, that were identified using environmental scanning, that could affect the technology shifty. For a quantitative assessment, trend extrapolations was used, specifically Holt's Linear Non-Seasonal Trend, to project a three-year forecast, based on the current data of a software solutions company. The technology foresight and resource demand forecast could be used by Resource and Capability Managers in the company for demand management, especially in tactical decision making for hiring, training, or redundancy.